Exploring an instructor’s teaching in the context of a research-based curriculum and ongoing professional development program - Bas-Ader, Sinem; Kertil, Mahmut; Carlson, Marilyn P. (Frontiers in Education, 2025)
Graduate teaching assistants (GTAs) play a critical role in undergraduate mathematics education, yet their advanced mathematical knowledge does not always translate into effective, student-centered instruction. This case study, situated within the Pathways Precalculus Curriculum and Professional Development (PPCPD) project, explores shifts in a GTA’s instructional practices across two consecutive semesters of teaching with Pathways materials at a large U.S. University. The study focuses on changes in the GTA’s use of quantitative and covariational reasoning, his efforts to engage students in these reasoning skills, and his evolving approach to teaching constant rate of change (CROC). Data sources included video-recorded lessons and two semi-structured interviews. Findings show the GTA became increasingly effective, spontaneous, and fluent in supporting students in constructing meaningful function formulas and graphs. We discuss how specific features of the PPCPD intervention may have contributed to these shifts. Implications for avenues for future research are offered.